A business-cycle model with cash and credit goods and a modified cash-in-advance feature: lessons for Bulgaria (1999-2020) - Vasiliev, Aleksandar (Model cyklu biznesowego z gotówką i towarami kredytowymi oraz zmodyfikowaną funkcją płatności zaliczkowej: przypadek Bułgarii (1999-2020), 2022)
The paper augments the standard business cycle model with cash and credit goods following Lucas and Stokey (1983, 1987), together with a modified cash-in-advance (CIA) considerations. In particular, the cash-in-advance constraint was extended to include private investment and government purchases. This specification was then calibrated to Bulgaria during the 1999-2020 period. The presence of cash and credit goods give a role to money in accentuating economic fluctuations. In particular, the two types of goods and the modified CIA constraint produce a more sophisticated propagation mechanism, with novel trade-offs faced by households. The model generates too volatile consumption, and countercyclical investment, which are at serious odds with the data. Overall, the model with cash and credit goods, and physical capital accumulation, did not provide a good framework to study business cycle fluctuations in Bulgaria.
Econometrics = Ekonometria, 2022, Vol. 26, No. 1, s. 1-13
Keywords: business cycles; cash and credit goods; modified cash-in-advance; constraint; Bulgaria; cykle koniunkturalne; gotówka i dobra kredytowe; zmodyfikowane ograniczenia płatności zaliczkowej; Bułgaria